OTORITAS JASA KEUANGAN (FINANCIAL SERVICES AUTHORITY) DAN INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Early Ridho Kismawadi (IAIN Langsa, 2016)
Supervision of the financial industry has a very important thing, it relates to the stability of theeconomy, it is necessary for an institution to regulate and supervise the financial industry ofbanks, and non bank financial industries . Before the Financial Services Authority (OJK) wasformed, Bank Indonesia served as macroprudential and microprudential supervisor, but with thepresence of Bank Indonesia OJK task can be focused to achieve and maintain rupiah stability. asthe new agency the OJK is still relatively not so well known, for it is in this paper will bedescribe the authority of the OJK and its relation with the supervision of Islamic banking inIndonesia .